Multipurpose redispersible latex powder and process for its preparation
Patent Information
- Application Number
- CN202611246204.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]但当前产品存在多场景适配短板:单一聚乙烯醇保护胶体使再分散乳液易分层沉淀,导致建材强度不均;普通二氧化硅填料与聚合物仅物理吸附,受力易脱粘,粘结强度衰减明显;聚合物亲水基团耐水强度保留率偏低,难适浸水场景;高湿环境下粉体易吸潮结块,影响施工;现有改进多为单一维度优化,无法兼顾再分散性、粘结力等多性能,难适配建材多场景、高可靠需求
本发明的多用途可再分散性乳胶粉及其制备方法,通过超声空化效应使氨基改性介孔二氧化硅均匀分散于水中,充分暴露其表面活性氨基位点;再利用复配乳化剂的胶束增溶作用,将复合单体乳化分散形成稳定预乳化液,酸性pH调节为后续自由基聚合提供适宜反应环境;之后采用种子聚合策略,先引发部分预乳化液形成聚合物种子核,再通过梯度滴加剩余预乳化液与引发剂,使单体在种子核表面聚合生长形成壳层,复合保护胶体协同乳化剂通过空间位阻与静电排斥作用稳定乳胶粒体系,最后加入改性二氧化硅分散液,借助其表面氨基与聚合物链的相互作用,实现无机填料与核-壳乳胶粒的紧密复合;最后通过弱碱性pH调节、真空脱气、喷雾干燥固化成粉,抗结块剂抑制粉体团聚,最终制得多用途可再分散性乳胶粉;其中通过分段滴加预乳化液、引发剂及复合保护胶体,梯度调控反应温度,实现了聚合物核-壳结构的精准构筑,复合保护胶体与乳化剂协同作用,显著提升乳胶粒的分散稳定性,而后期加入的改性二氧化硅分散液可通过氨基与聚合物链的相互作用,强化无机填料与有机基体的界面结合力,赋予乳液优异的力学性能与功能特性,抗结块剂的加入则有效防止粉体团聚,提升了乳胶粉的流动性与可再分散性,最终制得综合性能优异的多用途可再分散性乳胶粉;氨基改性介孔二氧化硅可强化有机-无机界面结合力,提升乳胶粉力学性能、耐水性与功能拓展性;复合保护胶体则协同稳定聚合体系,改善乳胶粉粒径均一性、再分散稳定性与成膜质量,延长储存保质期。
Smart Images

Figure REF-OBJ-1786955146062-000001
Abstract
Description
Technical Field
[0001] This invention relates to the field of latex powder, and more specifically to multipurpose redispersible latex powder and its preparation method. Background Technology
[0002] Redispersible latex powder is one of the core materials in the field of building polymer additives. It is produced by spray drying of polymer emulsion. After redispersing with water, it can form a stable emulsion, which can significantly improve the bonding strength, flexibility and workability of building materials such as building mortar, interior wall putty, tile adhesive, and exterior wall insulation plastering mortar. It is a key component for lightweight and high-performance in the modern building materials system.
[0003] However, current products have shortcomings in adaptability to multiple scenarios: the single polyvinyl alcohol protective colloid makes the redispersed emulsion prone to stratification and precipitation, resulting in uneven strength of building materials; ordinary silica filler and polymer are only physically adsorbed, and are prone to debonding under stress, with significant attenuation of bonding strength; the water resistance retention rate of polymer hydrophilic groups is low, making it difficult to adapt to water immersion scenarios; the powder is prone to moisture absorption and clumping in high humidity environments, affecting construction; existing improvements are mostly single-dimensional optimizations, which cannot take into account multiple properties such as redispersibility and adhesion, making it difficult to adapt to the multi-scenario and high reliability requirements of building materials. Summary of the Invention
[0004] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a multi-purpose redispersible latex powder and a method for preparing the same.
[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, this application provides a multipurpose redispersible latex powder comprising the following components in parts by weight: The mixture consists of 4-8 parts amino-modified mesoporous silica, 40-80 parts deionized water, 3-6 parts emulsifier, 50-100 parts composite monomer, 6-12 parts composite protective colloid mixture, 5-10 parts initiator solution, and 10-20 parts anti-caking agent. The amino-modified mesoporous silica is prepared by the following steps: Step a1: Add hydroxyethyl cellulose and deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen for protection. While stirring at 300-400 rpm, first raise the temperature to 60-65°C and stir for 30-35 minutes, then raise the temperature to 85-90°C and continue stirring for 2-2.2 hours. Then, while stirring, add sodium silicate aqueous solution dropwise at a rate of 1-2 drops / s. After the addition is complete, continue stirring for 30-35 minutes. Then, adjust the pH of the solution to 5-6 with hydrochloric acid and continue stirring for 2-2.2 hours. Cool to... At room temperature, the mixture was stirred for 24-25 hours at a stirring rate of 200-220 r / min, allowed to stand for aging for 24 hours, then centrifuged. The precipitate was transferred to a dialysis bag and dialyzed in distilled water for 5 days. The dialyzed precipitate was then transferred to a vacuum drying oven and vacuum dried at 55-60℃ for 12-13 hours. After grinding, the precipitate was passed through a 200-mesh sieve and then placed in a muffle furnace. The temperature was increased to 200℃ at a rate of 2℃ / min and held for 1 hour. The temperature was then increased to 550℃ at a rate of 5℃ / min and held for 6 hours. The mixture was then allowed to cool naturally to room temperature to obtain mesoporous silica powder. Step a2: Add mesoporous silica powder and anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Purge with nitrogen for protection and react at 75-80℃ and a stirring rate of 250-300 r / min for 30-35 min. Then, ultrasonically disperse at 300 W for 15-20 min. Cool to 60℃ while stirring, add 3-aminopropyltriethoxysilane, and then raise the temperature to 75-80℃. React for 6 minutes. After the reaction was completed, the mixture was transferred to a rotary evaporator at a temperature of 40-50℃ and a heating rate of 0.3℃ / min. The mixture was then rotary evaporated under a vacuum of -0.08MPa. After washing with isopropanol 2-3 times, the mixture was placed in a vacuum drying oven and dried at 55-60℃ for 12-13 hours. Then, it was placed in a forced-air drying oven and cured at 120℃ for 12 hours. After cooling to room temperature, the mixture was ground through a 200-mesh sieve to obtain amino-modified mesoporous silica.
[0006] As a further aspect of the present invention: the ratio of the amount of hydroxyethyl cellulose, deionized water and sodium silicate aqueous solution used in step a1 is 12-14g: 1.0-1.2L: 370-432mL.
[0007] As a further aspect of the present invention: the sodium silicate aqueous solution in step a1 is a solution prepared by mixing sodium silicate nonahydrate and deionized water in a ratio of 56.84g:368mL.
[0008] As a further aspect of the present invention: the concentration of hydrochloric acid in step a1 is 2 mol / L.
[0009] As a further aspect of the present invention: the dialysis bag in step a1 is selected from models with a molecular weight cutoff of 8000-14000 Da.
[0010] As a further aspect of the present invention: the ratio of the amount of mesoporous silica powder, anhydrous ethanol and 3-aminopropyltriethoxysilane used in step a2 is 2-4g: 100-200mL: 1.2-2.4mL.
[0011] The composite protective colloidal mixture is prepared by the following steps: Step b1: Add chitosan to acetic acid solution and stir for 6-7 hours at 25-30℃ and 200-220 rpm. Then transfer to a three-necked flask, purge with nitrogen, and place on a 50℃ constant-temperature magnetic stirrer. Adjust the stirring speed to 250-270 rpm. Adjust the pH to 4.5-5.0 with acetic acid solution. Add 5-hydroxymethylfurfural to anhydrous ethanol and sonicate for 10-12 minutes at 280-300W to form a pre-dispersion. Add the pre-dispersion dropwise to the three-necked flask, controlling the dropping rate. Add 1-2 drops / s, and continue stirring for 6 hours after the addition is complete. During the reaction, maintain the pH at 4.5-5.0. After the reaction is complete, allow it to cool naturally to room temperature. Add sodium hydroxide solution to adjust the pH to 8.0-8.5. Then transfer it to a Buchner funnel for vacuum filtration. First, wash the filter cake with deionized water, then wash it with isopropanol. Repeat the above vacuum filtration and washing operation 3 times. Then place the filter cake in a vacuum drying oven and dry it for 24-25 hours at a temperature of 55-60℃ and a vacuum of -0.08MPa. After grinding, pass it through a 200-mesh standard sieve to obtain modified chitosan. Step b2: Add the modified chitosan to a dilute acetic acid solution and ultrasonically disperse it for 30-35 minutes at a power of 300W. Adjust the pH to 6.5-7.0 with sodium hydroxide solution to obtain a colloidal solution. Add polyvinyl alcohol and deionized water to a beaker, heat to 85-90℃ and continue stirring for 60-70 minutes. Allow it to cool naturally to room temperature to obtain a polyvinyl alcohol solution. Mix the colloidal solution and the polyvinyl alcohol solution and stir for 20-30 minutes to obtain a composite protective colloidal mixture.
[0012] As a further embodiment of the present invention: the ratio of chitosan, acetic acid solution, 5-hydroxymethylfurfural and anhydrous ethanol in step b1 is 0.5-0.7g: 30-42mL: 0.38-0.53g: 10-14mL.
[0013] As a further aspect of the present invention: the degree of deacetylation of the chitosan in step b1 is 90%, and the molecular weight is 200,000 Da.
[0014] As a further aspect of the present invention: the mass fraction of the acetic acid solution in step b1 is 2%.
[0015] As a further aspect of the present invention: the mass fraction of the sodium hydroxide solution in step b1 is 5%.
[0016] As a further embodiment of the present invention: the ratio of modified chitosan, dilute acetic acid solution, polyvinyl alcohol and deionized water in step b2 is 1.5-1.7g: 75-85mL: 4.5-5.1g: 20.0-22.7mL.
[0017] As a further aspect of the present invention: the polyvinyl alcohol mentioned in step b2 is produced by Kuraray Japan, with the brand name PVA205 0588.
[0018] As a further aspect of the present invention: the mass fraction of the sodium hydroxide solution in step b2 is 5%; the mass fraction of the dilute acetic acid solution is 2%.
[0019] Secondly, this application provides a method for preparing a multi-purpose redispersible latex powder, comprising the following steps: Step 1: Weigh out 4-8 parts of amino-modified mesoporous silica, 40-80 parts of deionized water, 3-6 parts of emulsifier, 50-100 parts of composite monomer, 6-12 parts of composite protective colloid mixture, 5-10 parts of initiator solution and 10-20 parts of anti-caking agent according to the following weight proportions, and set aside. Step 2: Add amino-modified mesoporous silica and 1 / 4 deionized water to a beaker, place the beaker in a constant temperature water bath at 25-30℃, and ultrasonically disperse for 15-17 minutes under a power of 280-300W to obtain an amino-modified mesoporous silica dispersion. Step 3: Add 3 / 4 of the deionized water to a beaker. Under the conditions of 25-30℃ and 250-300r / min stirring speed, add the emulsifier and composite monomer in sequence, emulsify for 35-37min, and then adjust the pH to 5.0-5.5 with acetic acid solution to obtain the pre-emulsion. Step 4: Transfer 1 / 5 of the pre-emulsion to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Add 1 / 3 of the composite protective colloid mixture, purge with nitrogen for protection, and add 1 / 4 of the initiator solution at a temperature of 60-62℃ and a stirring rate of 220-250 r / min. React at a constant temperature for 35-37 min. Add the remaining 4 / 5 of the pre-emulsion and the remaining 3 / 4 of the initiator solution dropwise. Control the dropping rate of the pre-emulsion at 1-2 drops / s and the dropping rate of the initiator solution at 1 drop / 2s. During the dropping process, add the remaining 2 / 3 of the composite protective colloid mixture. After the dropping is complete, raise the temperature to 70-72℃ and maintain the temperature for 75-77 min. Add the amino-modified mesoporous silica dispersion dropwise and continue to maintain the temperature for 30-35 min to obtain a core-shell structured polymer emulsion. Step 5: Naturally cool the core-shell polymer emulsion to below 38℃, adjust the pH of the emulsion to 8.8-9.0 with sodium hydroxide solution, stir for 10-12 minutes, and let it stand for 5.5-5.7 hours. Then transfer it to a vacuum degassing machine and degas for 30-35 minutes at a temperature of 40℃ and a vacuum of -0.085MPa. Start the spray dryer and preheat it to the set parameters: inlet air temperature of 150℃, outlet air temperature of 80℃, atomizing disc speed of 24000r / min, and feed pump speed of 32r / min. Then pump it into the spray dryer for drying. Before degassing, filter the emulsion through a 200-mesh filter and cool it to room temperature. Then add an anti-caking agent and transfer it to a closed mixer. Mix for 18-20 minutes at a speed of 150-170r / min. After mixing, pass it through a 100-mesh sieve to obtain a multi-purpose redispersible latex powder.
[0020] As a further aspect of the present invention: the mass fraction of the acetic acid solution in step three is 2%.
[0021] As a further aspect of the present invention: the emulsifier in step three is a solution of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:1.5; the fatty alcohol polyoxyethylene ether is produced by BASF, model AEO-9.
[0022] As a further aspect of the present invention: the composite monomer in step three is a mixture of soft monomer, hard monomer, and functional monomer in a mass ratio of 25:16.7:8.3; the soft monomer is a mixture of butyl acrylate and isooctyl acrylate in a mass ratio of 1:1; the hard monomer is a mixture of methyl methacrylate and styrene in a mass ratio of 2:1; and the functional monomer is a mixture of glycidyl methacrylate and acrylamide in a mass ratio of 1:1.
[0023] As a further aspect of the present invention: the initiator solution in step four is a solution composed of ammonium persulfate, sodium bisulfite and deionized water in a ratio of 0.28g:0.22g:5mL.
[0024] As a further aspect of the present invention: the anti-caking agent in step five is a mixture of calcium stearate and 1250 mesh kaolin in a ratio of 1g:2g.
[0025] As a further aspect of the present invention: the mass fraction of the sodium hydroxide solution in step five is 5%.
[0026] The beneficial effects of this invention are: This invention relates to a multi-purpose redispersible latex powder and its preparation method. The method utilizes ultrasonic cavitation to uniformly disperse amino-modified mesoporous silica in water, fully exposing its surface-active amino sites. Then, the micellar solubilizing effect of a compound emulsifier is used to emulsify and disperse the composite monomers into a stable pre-emulsion. Acidic pH adjustment provides a suitable reaction environment for subsequent free radical polymerization. A seed polymerization strategy is then employed, first initiating a portion of the pre-emulsion to form polymer seed cores. The remaining pre-emulsion and initiator are then added in a gradient, allowing the monomers to polymerize and grow on the surface of the seed cores to form a shell. A composite protective colloid, in conjunction with the emulsifier, stabilizes the latex particle system through steric hindrance and electrostatic repulsion. Finally, a modified silica dispersion is added, utilizing the interaction between its surface amino groups and polymer chains to achieve a tight composite of inorganic fillers and core-shell latex particles. Finally, the powder is cured by weakly alkaline pH adjustment, vacuum degassing, and spray drying. An anti-caking agent inhibits powder agglomeration. A multi-purpose redispersible latex powder was prepared. This process involved staged addition of a pre-emulsion, initiator, and composite protective colloid, with gradient temperature control to achieve precise construction of the polymer core-shell structure. The composite protective colloid and emulsifier synergistically improved the dispersion stability of the latex particles. The later addition of modified silica dispersion strengthened the interfacial bonding between the inorganic filler and the organic matrix through the interaction between amino groups and polymer chains, endowing the emulsion with excellent mechanical properties and functional characteristics. The addition of an anti-caking agent effectively prevented powder agglomeration, improving the flowability and redispersibility of the latex powder. Ultimately, a multi-purpose redispersible latex powder with excellent overall performance was obtained. Amino-modified mesoporous silica strengthened the organic-inorganic interfacial bonding, improving the mechanical properties, water resistance, and functional extensibility of the latex powder. The composite protective colloid synergistically stabilized the polymerization system, improving the particle size uniformity, redispersibility, and film-forming quality of the latex powder, and extending its shelf life.
[0027] In the preparation of multi-purpose redispersible latex powder, an amino-modified mesoporous silica was first prepared. Hydroxyethyl cellulose was used as a soft template, which expanded into three-dimensional network micelles under staged heating and stirring. Sodium silicate was hydrolyzed under acidic conditions to generate a silicic acid precursor, which adsorbed onto the micelle surface via hydrogen bonds and cross-linked and condensed to form a silica-template complex. After aging and purification, the template was thermally decomposed and removed by high-temperature calcination, ultimately forming a silica powder with a regular mesoporous structure. Subsequently, the mesoporous silica was ultrasonically dispersed to increase the reaction interface. Under a nitrogen-protected reflux environment, the ethoxy group of 3-aminopropyltriethoxysilane first hydrolyzed to generate silanol groups, which then underwent a dehydration condensation reaction with the silanol groups on the silica surface to form a stable Si-O-Si complex. Covalent grafting of aminopropyl groups onto the powder surface, followed by washing, purification, and high-temperature curing to enhance graft stability, completes amino modification. Covalent grafting introduces active amino groups onto the surface of mesoporous silica, endowing the originally inert inorganic powder with the ability to chemically bond with subsequent modified chitosan, polymer monomers, and other organic components, significantly improving the inorganic-organic interfacial bonding. Furthermore, ultrasonic dispersion and mild reaction conditions preserve the high specific surface area and regular pore structure of mesoporous silica, allowing it to serve as a functional carrier and expand application scenarios. Simultaneously, high-temperature curing enhances the stability of the Si-O-Si covalent bonds, ensuring a long-lasting amino grafting effect and effectively preventing powder agglomeration in subsequent processes such as emulsion polymerization, thus improving the stability and overall performance of the composite system.
[0028] In the preparation of multipurpose redispersible latex powder, a composite protective colloid mixture was prepared. First, chitosan was dissolved in acetic acid solution. Under acidic, nitrogen-protected conditions, it underwent a Schiff base reaction (condensation of chitosan amino groups and 5-hydroxymethylfurfural aldehyde groups) with ultrasonically pre-dispersed 5-hydroxymethylfurfural to achieve modification. After the reaction, the alkalinity was adjusted to precipitate the modified chitosan, which was then washed and dried to obtain the modified product. Subsequently, the modified chitosan was ultrasonically dispersed in dilute acetic acid to form a colloid and adjusted to neutral. Polyvinyl alcohol was dissolved by high-temperature stirring and cooled to form a solution. The two were mixed and stirred to achieve uniform dispersion, ultimately forming the composite protective colloid mixture. The reaction was carried out by the reaction of 5-hydroxymethylfurfural with... Schiff base reaction of chitosan effectively modifies its water solubility and interfacial compatibility, solving the problem of easy aggregation of unmodified chitosan. Modified chitosan forms a stable colloid after ultrasonic dispersion and neutral pH adjustment. When combined with the polyvinyl alcohol solution formed after high-temperature dissolution, it produces a synergistic effect. This not only enhances the emulsifying ability and stability of the protective colloid, but also efficiently encapsulates latex particles and inhibits particle aggregation and flocculation in subsequent emulsion polymerization. Furthermore, the active groups of modified chitosan interact with components such as amino-modified mesoporous silica, further improving the interfacial bonding of the composite system. This lays the foundation for the preparation of high-performance core-shell structured polymer emulsions and latex powders. Detailed Implementation
[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] Example 1:
[0031] This embodiment describes a method for preparing multi-purpose redispersible latex powder, including the following steps: Step S1: Add 12g of hydroxyethyl cellulose and 1.0L of deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen for protection. While stirring at 300 rpm, first raise the temperature to 60℃ and stir for 30 min, then raise the temperature to 85℃ and continue stirring for 2 h. Then, while stirring, add 370mL of sodium silicate aqueous solution (a solution of sodium silicate nonahydrate and deionized water at a ratio of 56.84g:368mL), controlling the dropping rate at 1 drop / s. After the addition is complete, continue stirring for 30 min. Then, adjust the pH of the solution with 2mol / L hydrochloric acid. 5. Continue stirring for 2 hours, cool to room temperature, then continue stirring at a stirring rate of 200 r / min for 24 hours, let stand for aging for 24 hours, then centrifuge, transfer the precipitate to a dialysis bag (the dialysis bag is a model with a molecular weight cutoff of 8000 Da), dialyze in distilled water for 5 days, transfer the dialysis precipitate to a vacuum drying oven, vacuum dry at 55℃ for 12 hours, grind and pass through a 200-mesh sieve, then put it in a muffle furnace, heat to 200℃ at a heating rate of 2℃ / min, hold for 1 hour, heat to 550℃ at a heating rate of 5℃ / min, hold for 6 hours, and cool naturally to room temperature to obtain mesoporous silica powder; Step S2: Add 2g of mesoporous silica powder and 100mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Purge with nitrogen for protection and react at 75℃ and a stirring rate of 250r / min for 30min. Then, ultrasonically disperse at 300W for 15min. Cool to 60℃, keep stirring, add 1.2mL of 3-aminopropyltriethoxysilane, and then heat to 75℃ and react for 6h. After the reaction, transfer to a rotary evaporator at 40℃ and a heating rate of 0.3℃ / min for rotary evaporation under a vacuum of -0.08MPa. Wash twice with isopropanol, place in a vacuum drying oven, and dry at 55℃ for 12h. Then, place in a forced-air drying oven and cure at 120℃ for 12h. Cool to room temperature, grind through a 200-mesh sieve to obtain amino-modified mesoporous silica. Step S3: Add 0.5g of chitosan (degree of deacetylation of chitosan is 90%, molecular weight is 200,000 Da) to 30mL of 2% acetic acid solution. Stir for 6 hours at 25℃ and 200r / min. Then transfer to a three-necked flask, purge with nitrogen, and place on a 50℃ constant temperature magnetic stirrer. Adjust the stirring speed to 250r / min. Adjust the pH to 4.5 with 2% acetic acid solution. Add 0.38g of... 5-Hydroxymethylfurfural was added to 10 mL of anhydrous ethanol and sonicated for 10 min at 280 W to form a pre-dispersion. The pre-dispersion was added dropwise to a three-necked flask at a rate of 1 drop / s. After the addition was complete, the mixture was stirred for 6 h, and the pH was maintained at 4.5 during the reaction. After the reaction was complete, the mixture was allowed to cool naturally to room temperature. A 5% sodium hydroxide solution was added dropwise to adjust the pH to 8.0. The mixture was then transferred to a Buchner funnel for filtration. The mixture was first washed once with deionized water and then once with isopropanol. This filtration and washing process was repeated three times. The filter cake was then placed in a vacuum drying oven and dried for 24 h at 55 °C and -0.08 MPa. After grinding, the mixture was passed through a 200-mesh standard sieve to obtain modified chitosan. Step S4: Add 1.5g of modified chitosan to 75mL of 2% dilute acetic acid solution and ultrasonically disperse for 30min at 300W. Adjust the pH to 6.5 with 5% sodium hydroxide solution to obtain a colloidal solution. Add 4.5g of polyvinyl alcohol (PVA205 0588, manufactured by Kuraray, Japan) and 20.0mL of deionized water to a beaker, heat to 85℃ and stir for 60min. Allow to cool naturally to room temperature to obtain a polyvinyl alcohol solution. Mix the colloidal solution and the polyvinyl alcohol solution and stir for 20min to obtain a composite protective colloidal mixture. Step S5: Weigh out 4 parts by weight of amino-modified mesoporous silica, 40 parts of deionized water, 3 parts of emulsifier, 50 parts of composite monomer, 6 parts of composite protective colloid mixture, 5 parts of initiator solution and 10 parts of anti-caking agent, and set aside. Step S6: Add amino-modified mesoporous silica and 1 / 4 deionized water to a beaker, place the beaker in a constant temperature water bath at 25℃, and ultrasonically disperse for 15 minutes under a power of 280W to obtain an amino-modified mesoporous silica dispersion. Step S7: Add 3 / 4 of the deionized water to a beaker. Under conditions of 25°C and a stirring rate of 250 r / min, add the emulsifier (a solution of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:1.5, the fatty alcohol polyoxyethylene ether being produced by BASF, model AEO-9) and the composite monomer (a mixture of soft monomer, hard monomer, and functional monomer in a mass ratio of 25:16.7:8.3, the soft monomer being a mixture of butyl acrylate and isooctyl acrylate in a mass ratio of 1:1, the hard monomer being a mixture of methyl methacrylate and styrene in a mass ratio of 2:1, and the functional monomer being a mixture of glycidyl methacrylate and acrylamide in a mass ratio of 1:1). Emulsify for 35 min, then adjust the pH to 5.0 with a 2% acetic acid solution to obtain a pre-emulsion. Step S8: Transfer 1 / 5 of the pre-emulsion to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Add 1 / 3 of the composite protective colloid mixture, purge with nitrogen for protection, and add 1 / 4 of the initiator solution (the initiator solution is a mixture of ammonium persulfate, sodium bisulfite, and deionized water in a ratio of 0.28g:0.22g:5mL) at a temperature of 60℃ and a stirring rate of 220r / min. React at a constant temperature for 35min, then add the remaining 4 / 5 of the pre-emulsion and the remaining 3 / 4 of the initiator solution dropwise. The dropping rate of the pre-emulsion is controlled at 1 drop / s, and the dropping rate of the initiator solution is controlled at 1 drop / 2s. During the dropping process, add the remaining 2 / 3 of the composite protective colloid mixture. After the dropping is completed, raise the temperature to 70℃ and maintain the temperature for 75min. Add the amino-modified mesoporous silica dispersion dropwise and continue to maintain the temperature for 30min to obtain a core-shell structured polymer emulsion. Step S9: Naturally cool the core-shell polymer emulsion to below 38°C, adjust the pH of the emulsion to 8.8 with a 5% sodium hydroxide solution, stir for 10 min, and let it stand for 5.5 h. Then transfer it to a vacuum degassing machine and degas for 30 min at 40°C and a vacuum of -0.085 MPa. Start the spray dryer and preheat to the set parameters: inlet air temperature 150°C, outlet air temperature 80°C, and atomizing disc speed 24000 r. The feed pump speed is 32 r / min, and then it is pumped into the spray dryer for drying. Before degassing, the emulsion is filtered through a 200-mesh filter and cooled to room temperature. Then an anti-caking agent (calcium stearate and 1250-mesh kaolin mixed in a ratio of 1g:2g) is added to it. The mixture is then transferred to a closed mixer and mixed for 18 minutes at a speed of 150 r / min. After mixing, it is passed through a 100-mesh sieve to obtain multi-purpose redispersible latex powder.
[0032] Example 2:
[0033] This embodiment describes a method for preparing multi-purpose redispersible latex powder, including the following steps: Step S1: Add 13g of hydroxyethyl cellulose and 1.1L of deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen for protection. While stirring at 350 rpm, first raise the temperature to 63℃ and stir for 33 min, then raise the temperature to 87℃ and continue stirring for 2.1 h. Then, while stirring, add 401 mL of sodium silicate aqueous solution (a solution of sodium silicate nonahydrate and deionized water at a ratio of 56.84g:368mL), controlling the dropping rate at 1 drop / s. After the addition is complete, continue stirring for 33 min. Then, adjust the pH of the solution to 5.5 with 2 mol / L hydrochloric acid. Continue stirring for 2.1 h, cool to room temperature, then continue stirring at a stirring rate of 210 r / min for 24.5 h, let stand for aging for 24 h, then centrifuge, transfer the precipitate to a dialysis bag (the dialysis bag is selected with a molecular weight cutoff of 8000-14000 Da), dialyze in distilled water for 5 days, transfer the dialysis precipitate to a vacuum drying oven, vacuum dry at 57℃ for 12.5 h, grind and pass through a 200 mesh sieve, then put it in a muffle furnace, heat to 200℃ at a heating rate of 2℃ / min, hold for 1 h, heat to 550℃ at a heating rate of 5℃ / min, hold for 6 h, and cool naturally to room temperature to obtain mesoporous silica powder; Step S2: Add 3g of mesoporous silica powder and 150mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Purge with nitrogen for protection and react at 77℃ and a stirring rate of 270r / min for 33min. Then, ultrasonically disperse the mixture at 300W for 17min. Cool to 60℃, continue stirring, and add 1.8mL of... 3-Aminopropyltriethoxysilane was heated to 77°C and reacted for 6.5 h. After the reaction, the mixture was transferred to a rotary evaporator at 45°C and a heating rate of 0.3°C / min. The mixture was then rotary evaporated under a vacuum of -0.08 MPa. After washing three times with isopropanol, the mixture was placed in a vacuum drying oven and dried at 57°C for 12.5 h. Then, it was placed in a forced-air drying oven and cured at 120°C for 12 h. After cooling to room temperature, the mixture was ground through a 200-mesh sieve to obtain amino-modified mesoporous silica. Step S3: Add 0.6g of chitosan (degree of deacetylation of chitosan is 90%, molecular weight is 200,000 Da) to 36mL of 2% acetic acid solution. Stir for 6.5h at 27℃ and a stirring speed of 210r / min. Then transfer to a three-necked flask, purge with nitrogen, place on a 50℃ constant temperature magnetic stirrer, adjust the stirring speed to 260r / min, adjust the pH to 4.7 with 2% acetic acid solution, and add 0.45g of... 5-Hydroxymethylfurfural was added to 12 mL of anhydrous ethanol and sonicated for 11 min at 290 W to form a pre-dispersion. The pre-dispersion was added dropwise to a three-necked flask at a rate of 1 drop / s. After the addition was complete, the mixture was stirred for 6 h, and the pH was maintained at 4.7 during the reaction. After the reaction was complete, the mixture was allowed to cool naturally to room temperature. A 5% sodium hydroxide solution was added dropwise to adjust the pH to 8.3. The mixture was then transferred to a Buchner funnel for filtration. The mixture was first washed once with deionized water and then once with isopropanol. This filtration and washing process was repeated three times. The filter cake was then placed in a vacuum drying oven and dried for 24.5 h at 57 °C and -0.08 MPa. After grinding, the mixture was passed through a 200-mesh standard sieve to obtain modified chitosan. Step S4: Add 1.6g of modified chitosan to 80mL of 2% dilute acetic acid solution and ultrasonically disperse for 33min at 300W. Adjust the pH to 6.7 with 5% sodium hydroxide solution to obtain a colloidal solution. Add 4.8g of polyvinyl alcohol (PVA205 0588, manufactured by Kuraray, Japan) and 21.3mL of deionized water to a beaker, heat to 87℃ and stir for 65min. Allow to cool naturally to room temperature to obtain a polyvinyl alcohol solution. Mix the colloidal solution and the polyvinyl alcohol solution and stir for 25min to obtain a composite protective colloidal mixture. Step S5: Weigh out 6 parts by weight of amino-modified mesoporous silica, 60 parts by weight of deionized water, 4.5 parts by weight of emulsifier, 75 parts by weight of composite monomer, 9 parts by weight of composite protective colloid mixture, 7.5 parts by weight of initiator solution and 15 parts by weight of anti-caking agent, and set aside. Step S6: Add amino-modified mesoporous silica and 1 / 4 deionized water to a beaker, place the beaker in a constant temperature water bath at 27℃, and ultrasonically disperse for 16 minutes under a power of 290W to obtain an amino-modified mesoporous silica dispersion. Step S7: Add 3 / 4 of the deionized water to a beaker. Under conditions of 27°C and a stirring rate of 270 r / min, add the emulsifier (a solution of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:1.5, the fatty alcohol polyoxyethylene ether being produced by BASF, model AEO-9) and the composite monomer (a mixture of soft monomer, hard monomer, and functional monomer in a mass ratio of 25:16.7:8.3, the soft monomer being a mixture of butyl acrylate and isooctyl acrylate in a mass ratio of 1:1, the hard monomer being a mixture of methyl methacrylate and styrene in a mass ratio of 2:1, and the functional monomer being a mixture of glycidyl methacrylate and acrylamide in a mass ratio of 1:1). Emulsify for 36 min, then adjust the pH to 5.3 with a 2% acetic acid solution to obtain a pre-emulsion. Step S8: Transfer 1 / 5 of the pre-emulsion to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Add 1 / 3 of the composite protective colloid mixture, purge with nitrogen for protection, and add 1 / 4 of the initiator solution (the initiator solution is a mixture of ammonium persulfate, sodium bisulfite, and deionized water in a ratio of 0.28g:0.22g:5mL) at a temperature of 61℃ and a stirring rate of 230r / min. React at a constant temperature for 36min, then add the remaining 4 / 5 of the pre-emulsion and the remaining 3 / 4 of the initiator solution dropwise. The dropping rate of the pre-emulsion is controlled at 1 drop / s, and the dropping rate of the initiator solution is controlled at 1 drop / 2s. During the dropping process, add the remaining 2 / 3 of the composite protective colloid mixture. After the dropping is completed, raise the temperature to 71℃ and maintain the temperature for 76min. Add the amino-modified mesoporous silica dispersion dropwise and continue to maintain the temperature for 33min to obtain a core-shell structured polymer emulsion. Step S9: Naturally cool the core-shell polymer emulsion to below 38°C, adjust the pH of the emulsion to 8.9 with a 5% sodium hydroxide solution, stir for 11 min, and let it stand for 5.6 h. Then transfer it to a vacuum degassing machine and degas for 33 min at 40°C and a vacuum of -0.085 MPa. Start the spray dryer and preheat to the set parameters: inlet air temperature 150°C, outlet air temperature 80°C, and atomizing disc speed 24000 r. The feed pump speed is 32 r / min, and then it is pumped into the spray dryer for drying. Before degassing, the emulsion is filtered through a 200-mesh filter and cooled to room temperature. Then an anti-caking agent (calcium stearate and 1250-mesh kaolin mixed in a ratio of 1g:2g) is added to it. The mixture is then transferred to a closed mixer and mixed for 19 minutes at a speed of 160 r / min. After mixing, it is passed through a 100-mesh sieve to obtain multi-purpose redispersible latex powder.
[0034] Example 3:
[0035] This embodiment describes a method for preparing multi-purpose redispersible latex powder, including the following steps: Step S1: Add 14g of hydroxyethyl cellulose and 1.2L of deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen for protection. While stirring at 400 rpm, first raise the temperature to 65℃ and stir for 35 minutes, then raise the temperature to 90℃ and continue stirring for 2.2 hours. Then, while stirring, add 432mL of sodium silicate aqueous solution (a solution of sodium silicate nonahydrate and deionized water at a ratio of 56.84g:368mL), controlling the dropping rate at 2 drops / s. After the addition is complete, continue stirring for 35 minutes. Then, adjust the pH of the solution to [the desired concentration] with 2mol / L hydrochloric acid. 56. Continue stirring for 2.2 hours, cool to room temperature, then continue stirring at a stirring rate of 220 r / min for 25 hours, let stand for aging for 24 hours, then centrifuge, transfer the precipitate to a dialysis bag (the dialysis bag is a model with a molecular weight cutoff of 14000 Da), dialyze in distilled water for 5 days, transfer the dialysis precipitate to a vacuum drying oven, vacuum dry at 60℃ for 13 hours, grind and pass through a 200-mesh sieve, then put it in a muffle furnace, heat to 200℃ at a heating rate of 2℃ / min, hold for 1 hour, heat to 550℃ at a heating rate of 5℃ / min, hold for 6 hours, and cool naturally to room temperature to obtain mesoporous silica powder; Step S2: Add 4g of mesoporous silica powder and 200mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Purge with nitrogen for protection and react at 80℃ and a stirring rate of 300r / min for 35min. Then, ultrasonically disperse at 300W for 20min. Cool to 60℃, keep stirring, add 2.4mL of 3-aminopropyltriethoxysilane, and then heat to 80℃ and react for 7h. After the reaction, transfer to a rotary evaporator at 50℃ and a heating rate of 0.3℃ / min for rotary evaporation under a vacuum of -0.08MPa. Wash three times with isopropanol, place in a vacuum drying oven, and dry at 60℃ for 13h. Then, place in a forced-air drying oven and cure at 120℃ for 12h. Cool to room temperature, grind through a 200-mesh sieve to obtain amino-modified mesoporous silica. Step S3: Add 0.7g of chitosan (degree of deacetylation of chitosan is 90%, molecular weight is 200,000 Da) to 42mL of 2% acetic acid solution. Stir for 7 hours at 30℃ and a stirring speed of 220r / min. Then transfer to a three-necked flask, purge with nitrogen, and place on a 50℃ constant temperature magnetic stirrer. Adjust the stirring speed to 270r / min. Adjust the pH to 5.0 with 2% acetic acid solution. Add 0.53g of... 5-Hydroxymethylfurfural was added to 14 mL of anhydrous ethanol and sonicated for 12 min at 300 W to form a pre-dispersion. The pre-dispersion was added dropwise to a three-necked flask at a rate of 2 drops / s. After the addition was complete, the mixture was stirred for 6 h, and the pH was maintained at 5.0 during the reaction. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. A 5% sodium hydroxide solution was added dropwise to adjust the pH to 8.5. The mixture was then transferred to a Buchner funnel for filtration. The mixture was first washed once with deionized water and then once with isopropanol. This filtration and washing process was repeated three times. The filter cake was then placed in a vacuum drying oven and dried for 25 h at 60 °C and -0.08 MPa. After grinding, the mixture was passed through a 200-mesh standard sieve to obtain modified chitosan. Step S4: Add 1.7g of modified chitosan to 85mL of 2% dilute acetic acid solution and ultrasonically disperse for 35min at 300W. Adjust the pH to 7.0 with 5% sodium hydroxide solution to obtain a colloidal solution. Add 5.1g of polyvinyl alcohol (PVA205 0588, manufactured by Kuraray, Japan) and 22.7mL of deionized water to a beaker, heat to 90℃ and stir for 70min. Allow to cool naturally to room temperature to obtain a polyvinyl alcohol solution. Mix the colloidal solution and the polyvinyl alcohol solution and stir for 30min to obtain a composite protective colloidal mixture. Step S5: Weigh out 8 parts by weight of amino-modified mesoporous silica, 80 parts of deionized water, 6 parts of emulsifier, 100 parts of composite monomer, 12 parts of composite protective colloid mixture, 10 parts of initiator solution and 20 parts of anti-caking agent, and set aside. Step S6: Add amino-modified mesoporous silica and 1 / 4 deionized water to a beaker, place the beaker in a 30°C constant temperature water bath, and ultrasonically disperse for 17 minutes under a power of 300W to obtain an amino-modified mesoporous silica dispersion. Step S7: Add 3 / 4 of the deionized water to a beaker. Under conditions of 30°C and a stirring speed of 300 r / min, add the emulsifier (a solution of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:1.5, the fatty alcohol polyoxyethylene ether being produced by BASF, model AEO-9) and the composite monomer (a mixture of soft monomer, hard monomer, and functional monomer in a mass ratio of 25:16.7:8.3, the soft monomer being a mixture of butyl acrylate and isooctyl acrylate in a mass ratio of 1:1, the hard monomer being a mixture of methyl methacrylate and styrene in a mass ratio of 2:1, and the functional monomer being a mixture of glycidyl methacrylate and acrylamide in a mass ratio of 1:1). Emulsify for 37 min, then adjust the pH to 5.5 with a 2% acetic acid solution to obtain a pre-emulsion. Step S8: Transfer 1 / 5 of the pre-emulsion to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Add 1 / 3 of the composite protective colloid mixture, purge with nitrogen for protection, and add 1 / 4 of the initiator solution (the initiator solution is a mixture of ammonium persulfate, sodium bisulfite, and deionized water in a ratio of 0.28g:0.22g:5mL) at a temperature of 62℃ and a stirring rate of 250r / min. React at a constant temperature for 37min. Add the remaining 4 / 5 of the pre-emulsion and the remaining 3 / 4 of the initiator solution dropwise. Control the dropping rate of the pre-emulsion at 2 drops / s and the dropping rate of the initiator solution at 1 drop / 2s. During the dropping process, add the remaining 2 / 3 of the composite protective colloid mixture. After the dropping is complete, raise the temperature to 72℃ and maintain the temperature for 77min. Add the amino-modified mesoporous silica dispersion dropwise and continue to maintain the temperature for 35min to obtain a core-shell structured polymer emulsion. Step S9: Naturally cool the core-shell polymer emulsion to below 38°C, adjust the pH of the emulsion to 9.0 with a 5% sodium hydroxide solution, stir for 12 minutes, and let it stand for 5.7 hours. Then transfer it to a vacuum degassing machine and degas for 35 minutes at 40°C and a vacuum of -0.085 MPa. Start the spray dryer and preheat it to the set parameters: inlet air temperature 150°C, outlet air temperature 80°C, and atomizing disc speed 24000 r / min. The feed pump speed is 32 r / min, and then it is pumped into the spray dryer for drying. Before degassing, the emulsion is filtered through a 200-mesh filter and cooled to room temperature. Then an anti-caking agent (calcium stearate and 1250-mesh kaolin mixed in a ratio of 1g:2g) is added to it. The mixture is then transferred to a closed mixer and mixed for 20 minutes at a speed of 170 r / min. After mixing, it is passed through a 100-mesh sieve to obtain multi-purpose redispersible latex powder.
[0036] Comparative Example 1: This comparative example illustrates a method for preparing a multi-purpose redispersible latex powder, comprising the following steps: Step S1: Add 0.5g of chitosan (degree of deacetylation of chitosan is 90%, molecular weight is 200,000 Da) to 30mL of 2% acetic acid solution. Stir for 6 hours at 25℃ and 200r / min. Then transfer to a three-necked flask, purge with nitrogen, and place on a 50℃ constant temperature magnetic stirrer. Adjust the stirring speed to 250r / min. Adjust the pH to 4.5 with 2% acetic acid solution. Add 0.38g of... 5-Hydroxymethylfurfural was added to 10 mL of anhydrous ethanol and sonicated for 10 min at 280 W to form a pre-dispersion. The pre-dispersion was added dropwise to a three-necked flask at a rate of 1 drop / s. After the addition was complete, the mixture was stirred for 6 h, and the pH was maintained at 4.5 during the reaction. After the reaction was complete, the mixture was allowed to cool naturally to room temperature. A 5% sodium hydroxide solution was added dropwise to adjust the pH to 8.0. The mixture was then transferred to a Buchner funnel for filtration. The mixture was first washed once with deionized water and then once with isopropanol. This filtration and washing process was repeated three times. The filter cake was then placed in a vacuum drying oven and dried for 24 h at 55 °C and -0.08 MPa. After grinding, the mixture was passed through a 200-mesh standard sieve to obtain modified chitosan. Step S2: Add 1.5g of modified chitosan to 75mL of 2% dilute acetic acid solution and ultrasonically disperse for 30min at 300W. Adjust the pH to 6.5 with 5% sodium hydroxide solution to obtain a colloidal solution. Add 4.5g of polyvinyl alcohol (PVA205 0588, manufactured by Kuraray, Japan) and 20.0mL of deionized water to a beaker, heat to 85℃ and stir for 60min. Allow to cool naturally to room temperature to obtain a polyvinyl alcohol solution. Mix the colloidal solution and the polyvinyl alcohol solution and stir for 20min to obtain a composite protective colloidal mixture. Step S3: Weigh out 4 parts by weight of silica, 40 parts by weight of deionized water, 3 parts by weight of emulsifier, 50 parts by weight of composite monomer, 6 parts by weight of composite protective colloid mixture, 5 parts by weight of initiator solution and 10 parts by weight of anti-caking agent, and set aside. Step S4: Add silica and 1 / 4 deionized water to a beaker, place the beaker in a 25°C constant temperature water bath, and ultrasonically disperse for 15 minutes at a power of 280W to obtain a silica dispersion. Step S5: Add 3 / 4 of the deionized water to a beaker. Under conditions of 25°C and a stirring rate of 250 r / min, add the emulsifier (a solution of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:1.5, the fatty alcohol polyoxyethylene ether being produced by BASF, model AEO-9) and the composite monomer (a mixture of soft monomer, hard monomer, and functional monomer in a mass ratio of 25:16.7:8.3, the soft monomer being a mixture of butyl acrylate and isooctyl acrylate in a mass ratio of 1:1, the hard monomer being a mixture of methyl methacrylate and styrene in a mass ratio of 2:1, and the functional monomer being a mixture of glycidyl methacrylate and acrylamide in a mass ratio of 1:1). Emulsify for 35 min, then adjust the pH to 5.0 with a 2% acetic acid solution to obtain a pre-emulsion. Step S6: Transfer 1 / 5 of the pre-emulsion to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Add 1 / 3 of the composite protective colloid mixture, purge with nitrogen for protection, and add 1 / 4 of the initiator solution (the initiator solution is a mixture of ammonium persulfate, sodium bisulfite, and deionized water in a ratio of 0.28g:0.22g:5mL) at a temperature of 60℃ and a stirring rate of 220r / min. React at a constant temperature for 35min, then add the remaining 4 / 5 of the pre-emulsion and the remaining 3 / 4 of the initiator solution dropwise. The dropping rate of the pre-emulsion is controlled at 1 drop / s, and the dropping rate of the initiator solution is controlled at 1 drop / 2s. During the dropping process, add the remaining 2 / 3 of the composite protective colloid mixture. After the dropping is completed, raise the temperature to 70℃ and maintain the temperature for 75min. Add the silica dispersion dropwise and continue to maintain the temperature for 30min to obtain a core-shell structured polymer emulsion. Step S7: Naturally cool the core-shell polymer emulsion to below 38°C, adjust the pH of the emulsion to 8.8 with a 5% sodium hydroxide solution, stir for 10 min, let it stand for 5.5 h, then transfer it to a vacuum degassing machine and degas for 30 min at 40°C and a vacuum of -0.085 MPa. Start the spray dryer and preheat to the set parameters: inlet air temperature 150°C, outlet air temperature 80°C, and atomizing disc speed 24000 r. The feed pump speed is 32 r / min, and then it is pumped into the spray dryer for drying. Before degassing, the emulsion is filtered through a 200-mesh filter and cooled to room temperature. Then an anti-caking agent (calcium stearate and 1250-mesh kaolin mixed in a ratio of 1g:2g) is added to it. The mixture is then transferred to a closed mixer and mixed for 18 minutes at a speed of 150 r / min. After mixing, it is passed through a 100-mesh sieve to obtain multi-purpose redispersible latex powder.
[0037] Comparative Example 2: This comparative example illustrates a method for preparing a multi-purpose redispersible latex powder, comprising the following steps: Step S1: Add 12g of hydroxyethyl cellulose and 1.0L of deionized water to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant-pressure dropping funnel. Purge with nitrogen for protection. While stirring at 300 rpm, first raise the temperature to 60℃ and stir for 30 min, then raise the temperature to 85℃ and continue stirring for 2 h. Then, while stirring, add 370mL of sodium silicate aqueous solution (a solution of sodium silicate nonahydrate and deionized water at a ratio of 56.84g:368mL), controlling the dropping rate at 1 drop / s. After the addition is complete, continue stirring for 30 min. Then, adjust the pH of the solution with 2mol / L hydrochloric acid. 5. Continue stirring for 2 hours, cool to room temperature, then continue stirring at a stirring rate of 200 r / min for 24 hours, let stand for aging for 24 hours, then centrifuge, transfer the precipitate to a dialysis bag (the dialysis bag is a model with a molecular weight cutoff of 8000 Da), dialyze in distilled water for 5 days, transfer the dialysis precipitate to a vacuum drying oven, vacuum dry at 55℃ for 12 hours, grind and pass through a 200-mesh sieve, then put it in a muffle furnace, heat to 200℃ at a heating rate of 2℃ / min, hold for 1 hour, heat to 550℃ at a heating rate of 5℃ / min, hold for 6 hours, and cool naturally to room temperature to obtain mesoporous silica powder; Step S2: Add 2g of mesoporous silica powder and 100mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Purge with nitrogen for protection and react at 75℃ and a stirring rate of 250r / min for 30min. Then, ultrasonically disperse at 300W for 15min. Cool to 60℃, keep stirring, add 1.2mL of 3-aminopropyltriethoxysilane, and then heat to 75℃ and react for 6h. After the reaction, transfer to a rotary evaporator at 40℃ and a heating rate of 0.3℃ / min for rotary evaporation under a vacuum of -0.08MPa. Wash twice with isopropanol, place in a vacuum drying oven, and dry at 55℃ for 12h. Then, place in a forced-air drying oven and cure at 120℃ for 12h. Cool to room temperature, grind through a 200-mesh sieve to obtain amino-modified mesoporous silica. Step S3: Add 4.5g of polyvinyl alcohol (polyvinyl alcohol is produced by Kuraray, Japan, brand name PVA205 0588) and 20.0mL of deionized water to a beaker, heat to 85℃ and continue stirring for 60min, then cool naturally to room temperature to obtain a polyvinyl alcohol solution. Step S4: Weigh out 4 parts of amino-modified mesoporous silica, 40 parts of deionized water, 3 parts of emulsifier, 50 parts of composite monomer, 6 parts of polyvinyl alcohol solution, 5 parts of initiator solution and 10 parts of anti-caking agent according to the weight ratio, and set aside. Step S5: Add amino-modified mesoporous silica and 1 / 4 deionized water to a beaker, place the beaker in a constant temperature water bath at 25℃, and ultrasonically disperse for 15 minutes under a power of 280W to obtain an amino-modified mesoporous silica dispersion. Step S6: Add 3 / 4 of the deionized water to a beaker. Under conditions of 25°C and a stirring rate of 250 r / min, add the emulsifier (a solution of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:1.5, the fatty alcohol polyoxyethylene ether being produced by BASF, model AEO-9) and the composite monomer (a mixture of soft monomer, hard monomer, and functional monomer in a mass ratio of 25:16.7:8.3, the soft monomer being a mixture of butyl acrylate and isooctyl acrylate in a mass ratio of 1:1, the hard monomer being a mixture of methyl methacrylate and styrene in a mass ratio of 2:1, and the functional monomer being a mixture of glycidyl methacrylate and acrylamide in a mass ratio of 1:1). Emulsify for 35 min, then adjust the pH to 5.0 with a 2% acetic acid solution to obtain a pre-emulsion. Step S7: Transfer 1 / 5 of the pre-emulsion to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Add 1 / 3 of the polyvinyl alcohol solution and purge with nitrogen for protection. Under conditions of 60°C and a stirring rate of 220 r / min, add 1 / 4 of the initiator solution (the initiator solution is a mixture of ammonium persulfate, sodium bisulfite, and deionized water in a ratio of 0.28 g: 0.22 g: 5 mL). React at a constant temperature for 35 min. Add the remaining 4 / 5 of the pre-emulsion and the remaining 3 / 4 of the initiator solution dropwise. Control the dropping rate of the pre-emulsion at 1 drop / s and the dropping rate of the initiator solution at 1 drop / 2s. During the dropping process, add the remaining 2 / 3 of the polyvinyl alcohol solution. After the dropping is completed, raise the temperature to 70°C and maintain the temperature for 75 min. Add the amino-modified mesoporous silica dispersion dropwise and continue to maintain the temperature for 30 min to obtain a core-shell structured polymer emulsion. Step S8: Naturally cool the core-shell polymer emulsion to below 38°C, adjust the pH of the emulsion to 8.8 with a 5% sodium hydroxide solution, stir for 10 minutes, let it stand for 5.5 hours, then transfer it to a vacuum degassing machine and degas for 30 minutes at 40°C and a vacuum of -0.085 MPa. Start the spray dryer and preheat to the set parameters: inlet air temperature 150°C, outlet air temperature 80°C, and atomizing disc speed 24000 r / min. The feed pump speed is 32 r / min, and then it is pumped into the spray dryer for drying. Before degassing, the emulsion is filtered through a 200-mesh filter and cooled to room temperature. Then an anti-caking agent (calcium stearate and 1250-mesh kaolin mixed in a ratio of 1g:2g) is added to it. The mixture is then transferred to a closed mixer and mixed for 18 minutes at a speed of 150 r / min. After mixing, it is passed through a 100-mesh sieve to obtain multi-purpose redispersible latex powder.
[0038] Comparative Example 3: This comparative example illustrates a method for preparing a multi-purpose redispersible latex powder, comprising the following steps: Step S1: Add 4.5g of polyvinyl alcohol (polyvinyl alcohol is produced by Kuraray, Japan, brand name PVA205 0588) and 20.0mL of deionized water to a beaker, heat to 85℃ and continue stirring for 60min, then cool naturally to room temperature to obtain a polyvinyl alcohol solution. Step S2: Weigh out 4 parts by weight of silica, 40 parts by weight of deionized water, 3 parts by weight of emulsifier, 50 parts by weight of composite monomer, 6 parts by weight of polyvinyl alcohol solution, 5 parts by weight of initiator solution and 10 parts by weight of anti-caking agent, and set aside. Step S3: Add silica and 1 / 4 deionized water to a beaker, place the beaker in a 25°C constant temperature water bath, and ultrasonically disperse for 15 minutes at a power of 280W to obtain a silica dispersion. Step S4: Add 3 / 4 of the deionized water to a beaker. Under conditions of 25°C and a stirring rate of 250 r / min, add the emulsifier (a solution of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:1.5, the fatty alcohol polyoxyethylene ether being produced by BASF, model AEO-9) and the composite monomer (a mixture of soft monomer, hard monomer, and functional monomer in a mass ratio of 25:16.7:8.3, the soft monomer being a mixture of butyl acrylate and isooctyl acrylate in a mass ratio of 1:1, the hard monomer being a mixture of methyl methacrylate and styrene in a mass ratio of 2:1, and the functional monomer being a mixture of glycidyl methacrylate and acrylamide in a mass ratio of 1:1). Emulsify for 35 min, then adjust the pH to 5.0 with a 2% acetic acid solution to obtain a pre-emulsion. Step S5: Transfer 1 / 5 of the pre-emulsion to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and constant pressure dropping funnel. Add 1 / 3 of the polyvinyl alcohol solution, purge with nitrogen for protection, and add 1 / 4 of the initiator solution (the initiator solution is a mixture of ammonium persulfate, sodium bisulfite, and deionized water in a ratio of 0.28g:0.22g:5mL) at a temperature of 60℃ and a stirring rate of 220r / min. React at a constant temperature for 35min. Add the remaining 4 / 5 of the pre-emulsion and the remaining 3 / 4 of the initiator solution dropwise. Control the dropping rate of the pre-emulsion at 1 drop / s and the dropping rate of the initiator solution at 1 drop / 2s. During the dropping process, add the remaining 2 / 3 of the polyvinyl alcohol solution. After the dropping is complete, raise the temperature to 70℃ and maintain the temperature for 75min. Add the silica dispersion dropwise and continue to maintain the temperature for 30min to obtain a core-shell structured polymer emulsion. Step S6: Naturally cool the core-shell polymer emulsion to below 38°C, adjust the pH of the emulsion to 8.8 with a 5% sodium hydroxide solution, stir for 10 minutes, and let it stand for 5.5 hours. Then transfer it to a vacuum degassing machine and degas for 30 minutes at 40°C and a vacuum of -0.085 MPa. Start the spray dryer and preheat it to the set parameters: inlet air temperature 150°C, outlet air temperature 80°C, and atomizing disc speed 24000 r / min. The feed pump speed is 32 r / min, and then it is pumped into the spray dryer for drying. Before degassing, the emulsion is filtered through a 200-mesh filter and cooled to room temperature. Then an anti-caking agent (calcium stearate and 1250-mesh kaolin mixed in a ratio of 1g:2g) is added to it. The mixture is then transferred to a closed mixer and mixed for 18 minutes at a speed of 150 r / min. After mixing, it is passed through a 100-mesh sieve to obtain multi-purpose redispersible latex powder.
[0039] Performance testing: The multipurpose redispersible latex powders of Examples 1-3 and Comparative Examples 1-3 were tested according to the following methods; Redispersion stability test: Weigh 5g of sample, add 45g of deionized water, stir for 30min at 25℃ and 200r / min, then let stand for 24h, observe the emulsion layering / precipitation phenomenon, and record the height of the upper clear liquid.
[0040] Bond strength test: At room temperature, 40mm×40mm×160mm specimens were prepared according to the mass ratio of latex powder to cement mortar = 1:10. After standard curing for 7 days, the tensile bond strength was tested using a universal testing machine.
[0041] Water resistance bond strength retention rate test: The specimens cured for 7 days were immersed in water for 48 hours, and after the surface moisture was wiped dry, the tensile bond strength was tested, and the retention rate was calculated (water resistance strength / room temperature strength × 100%).
[0042] Film-forming flexibility test: The redispersible latex powder was coated onto a polytetrafluoroethylene plate and formed a film at room temperature for 48 hours (film thickness approximately 0.3 mm). The film was then bent at 25°C, and the minimum bending radius without cracks was recorded.
[0043] Storage stability test: The sample was stored in a 40℃ oven for 30 days, and the clumping was observed. The clumping rate was calculated as (mass of clumped sample / total mass × 100%).
[0044] The test results are shown in Table 1: Table 1: Test Results Summary Table
[0045] Referring to Table 1, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the multipurpose redispersible latex powder has excellent redispersibility, high bond strength, good film-forming flexibility, and storage stability.
[0046] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0047] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A multi-purpose redispersible latex powder, characterized in that, Includes the following components by weight: The mixture consists of 4-8 parts amino-modified mesoporous silica, 40-80 parts deionized water, 3-6 parts emulsifier, 50-100 parts composite monomer, 6-12 parts composite protective colloid mixture, 5-10 parts initiator solution, and 10-20 parts anti-caking agent. The amino-modified mesoporous silica is prepared by the following steps: Step a1: Mix hydroxyethyl cellulose and deionized water, heat and stir, then add sodium silicate aqueous solution, continue stirring and reacting, then adjust pH, continue stirring, cool, continue stirring, let stand for aging, then centrifuge, dialyze, vacuum dry, grind and sieve, then sinter and cool to obtain mesoporous silica powder. Step a2: Mix mesoporous silica powder and anhydrous ethanol, continue the reaction, then disperse by ultrasonication, cool, add 3-aminopropyltriethoxysilane, then heat up and react, after the reaction is complete, rotary evaporate, then wash, dry, high temperature solidify, cool, grind and sieve to obtain amino-modified mesoporous silica.
2. The multipurpose redispersible latex powder according to claim 1, characterized in that, In step a1, the ratio of hydroxyethyl cellulose, deionized water, and sodium silicate aqueous solution is 12-14g: 1.0-1.2L: 370-432mL; the sodium silicate aqueous solution is a solution prepared by mixing sodium silicate nonahydrate and deionized water in a ratio of 56.84g: 368mL; the dialysis bag is selected with a molecular weight cutoff of 8000-14000Da.
3. The multipurpose redispersible latex powder according to claim 1, characterized in that, The ratio of the amount of mesoporous silica powder, anhydrous ethanol and 3-aminopropyltriethoxysilane used in step a2 is 2-4g: 100-200mL: 1.2-2.4mL.
4. The multipurpose redispersible latex powder according to claim 1, characterized in that, The composite protective colloidal mixture is prepared by the following steps: Step b1: Add chitosan to acetic acid solution, stir, then transfer to a three-necked flask, adjust the pH value, add 5-hydroxymethylfurfural to anhydrous ethanol and sonicate to form a pre-dispersion, add the pre-dispersion dropwise to the three-necked flask, continue stirring the reaction, after the reaction is completed, cool, adjust the pH value, then repeat the suction filtration and washing operation, then dry, grind and sieve to obtain modified chitosan; Step b2: Add modified chitosan to dilute acetic acid solution and disperse it by ultrasonication. Adjust the pH to obtain a colloidal solution. Add polyvinyl alcohol and deionized water to a beaker, continue stirring, and cool to obtain a polyvinyl alcohol solution. Mix the colloidal solution and the polyvinyl alcohol solution to obtain a composite protective colloidal mixture.
5. The multipurpose redispersible latex powder according to claim 4, characterized in that, In step b1, the ratio of chitosan, acetic acid solution, 5-hydroxymethylfurfural, and anhydrous ethanol is 0.5-0.7g: 30-42mL: 0.38-0.53g: 10-14mL; the mass fraction of the acetic acid solution is 2%; the degree of deacetylation of the chitosan is 90%, and the molecular weight is 200,000 Da.
6. The multipurpose redispersible latex powder according to claim 4, characterized in that, In step b2, the ratio of modified chitosan, dilute acetic acid solution, polyvinyl alcohol, and deionized water is 1.5-1.7g: 75-85mL: 4.5-5.1g: 20.0-22.7mL; the mass fraction of the dilute acetic acid solution is 2%.
7. A method for preparing multi-purpose redispersible latex powder, characterized in that, The method for preparing the multipurpose redispersible latex powder as described in any one of claims 1-6 comprises the following steps: Step 1: Weigh out 4-8 parts of amino-modified mesoporous silica, 40-80 parts of deionized water, 3-6 parts of emulsifier, 50-100 parts of composite monomer, 6-12 parts of composite protective colloid mixture, 5-10 parts of initiator solution and 10-20 parts of anti-caking agent according to the following weight proportions, and set aside. Step 2: Add amino-modified mesoporous silica and 1 / 4 deionized water to a beaker and disperse by ultrasonication to obtain an amino-modified mesoporous silica dispersion. Step 3: Add 3 / 4 of the deionized water to the beaker, then add the emulsifier and the complex monomer in sequence, emulsify, and then adjust the pH to obtain the pre-emulsion. Step 4: Transfer 1 / 5 of the pre-emulsion to a three-necked flask, add 1 / 3 of the composite protective colloid mixture, add 1 / 4 of the initiator solution, and react at a constant temperature. Add the remaining 4 / 5 of the pre-emulsion and the remaining 3 / 4 of the initiator solution dropwise. During the dropwise addition, add the remaining 2 / 3 of the composite protective colloid mixture. After the dropwise addition is complete, raise the temperature and maintain the reaction temperature. Add the amino-modified mesoporous silica dispersion dropwise and continue to maintain the reaction temperature to obtain a core-shell structured polymer emulsion. Step 5: Cool the core-shell polymer emulsion, adjust the pH, stir and let it stand, then degas it, start the spray dryer, and then pump it into the spray dryer for drying. Filter the emulsion with a filter screen before degassing, cool it, then add an anti-caking agent, transfer it to a closed mixer for mixing, and after mixing, sieve it to obtain a multi-purpose redispersible latex powder.
8. The method for preparing the multi-purpose redispersible latex powder according to claim 7, characterized in that, The emulsifier in step three is a solution of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:1.5; the composite monomer is a mixture of soft monomer, hard monomer and functional monomer in a mass ratio of 25:16.7:8.3; the soft monomer is a mixture of butyl acrylate and isooctyl acrylate in a mass ratio of 1:1; the hard monomer is a mixture of methyl methacrylate and styrene in a mass ratio of 2:1; the functional monomer is a mixture of glycidyl methacrylate and acrylamide in a mass ratio of 1:
1.
9. The method for preparing the multi-purpose redispersible latex powder according to claim 7, characterized in that, The initiator solution in step four is a solution prepared by mixing ammonium persulfate, sodium bisulfite and deionized water in a ratio of 0.28g:0.22g:5mL.
10. The method for preparing the multipurpose redispersible latex powder according to claim 7, characterized in that, The anti-caking agent mentioned in step five is a mixture of calcium stearate and 1250 mesh kaolin in a ratio of 1g:2g.